The Fundamental Groups of Open Manifolds with Nonnegative Ricci Curvature - Pan, Jiayin (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
We survey the results on fundamental groups of open manifolds with nonnegative Ricci curvature. We also present some open questions on this topic.